2015
DOI: 10.1016/j.bbadis.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Activated STING enhances Tregs infiltration in the HPV-related carcinogenesis of tongue squamous cells via the c-jun/CCL22 signal

Abstract: The negative role of the activated stimulator of IFN genes (STING) has been uncovered in autoinflammatory disease and cancer. However, the role of STING in virus-related carcinogenesis is not well known. Herein, HPV(+) tongue squamous cell carcinoma (TSCC) (n=25) and HPV(-) TSCC samples (n=25) were randomly collected and were verified by in situ hybridization (ISH) and p16 immunohistochemistry (IHC) to assess the expression and activated status of STING through IHC. The results showed that the expression of ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 37 publications
1
92
2
Order By: Relevance
“…ES is short for enrichment score controls immune cell trafficking in reaction to inflammatory stimuli, hence determining the metastasis of HNSCC cells in vivo [21]. CCL22, an immunosuppressive cytokine, facilitates Tregs infiltration in the HPV-related tongue squamous cell carcinoma [27]. The most significant biological processes that appear to negatively correlate with the immune risk are IFN-α responses, IFN-γ responses, IL-2/STAT5 signaling and IL-6/JAK/STAT3 signaling, all of which were associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…ES is short for enrichment score controls immune cell trafficking in reaction to inflammatory stimuli, hence determining the metastasis of HNSCC cells in vivo [21]. CCL22, an immunosuppressive cytokine, facilitates Tregs infiltration in the HPV-related tongue squamous cell carcinoma [27]. The most significant biological processes that appear to negatively correlate with the immune risk are IFN-α responses, IFN-γ responses, IL-2/STAT5 signaling and IL-6/JAK/STAT3 signaling, all of which were associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, STING down-regulation in the tumor microenvironment has been associated with tumor-igenesis and poor prognosis in melanoma, colorectal and gastric cancers [1618]. .In HNSCC, STING was found to be activated in HPV + tumor specimens [19]. Other studies revealed that the HPV oncoprotein E7 inhibits STING signaling pathway by blocking its interaction with IRF3 raising a question regarding the role of STING in HNSCC [7,20], and EGFR signaling was shown to modulate phosphorylation of IRF3 and TBK1 [21].…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The aberrant expression of miRNA and LncRNA was found to be involved into the progression of cancer. [6][7][8][9] miR-34 and let-7 were found to be tumoursuppressive miRNAs in lung cancer, systemic nano-delivery of miR-34…”
mentioning
confidence: 99%